Implementation of the Role of Peacemakers in Bridging Differences in Beliefs: A Christian Educator's Perspective - La'ia, Dewi; Santo, Joseph Christ (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
Indonesia is a nation significantly rich in cultural, ethnic, and religious diversity. While this diversity is a source of strength, it also presents challenges in fostering social harmony. This study examines the implementation of the peacemaker concept in bridging differences in beliefs, based on Jesus' teachings in Matthew 5:9. Using a qualitative method with a literature review approach (library research), the research explores relevant websites, journals, and books to analyze the biblical meaning of